Antiviral Activitiy of Curcumin, Demethoxycurcumin, Bisdemethoxycurcumin and Cyclocurcumin compounds of Curcuma longa against NSP3 on SARS-CoV-2 - Hidayah, Rizka Nurul; Nafisa, Belia Bima; 'Arifin, Miftah Saiful; Santosaningsih, Dewi; Muti'ah, Roihatul (Indonesian Society for Cancer Chemoprevention, 2022)
SARS-CoV-2 genome encodes two large polyproteins (pp), pp1a and pp1ab which are cleaved and transformed into a mature form by a protease, non-structural protein 3 (NSP3). NSP3 is encoded by open reading frame (ORF) 1a/b. Curcuma longa (C. longa) or turmeric has been documented to have antiviral effects. The aim of this study was to assess the viral activities of C. longa against SARS-CoV-2 focusing on its potency to inhibit viral replication by targeting NSP3. PubChem databases were used to obtain the metabolic profile of C. longa. The compound's interaction with nucleocapsid was analyzed using molecular docking with Molegro Virtual Docker. Bioinformatics analysis based on rerank score presents all compounds of C. longa have higher binding affinity than the native ligand with cyclocurcumin as the lowest score (-128.38 kcal/mol). This anti-viral activity was hypothesized from the similarity of hydrogen bonds with amino acid residues Ser 128 and Asn 40 as key residues present in Ribavirin. This study reveals that C. longa is the potential to be developed as an antiviral agent through replication inhibition in SARS-CoV-2 targeting its replication mediated by NSP3.Keywords: C. longa, Non-Structural Protein 3, COVID-19.